Parotid secretory carcinoma: a rare entity in a young patient - Rusli, Muhammad F.; Lim, Sin W. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Secretory carcinoma (SC) of the parotid gland is a rare malignancy of the head and neck that presents almost equally in both genders with the average age of presentation in the mid-40. SC is often misdiagnosed as salivary acinic cell carcinoma (AciCC) as they share similar pathological morphology which is difficult to differentiate based on staining alone. We present a case of a 22-year-old female with this uncommon pathology who underwent subtotal parotidectomy after a conflicting provisional diagnosis of a benign tumor based on cytology and CT scan reporting possible malignancy involving the deep parotid lobe. It was later confirmed as SC on histopathology examination.